DIMENSI CINTA DALAM CERPEN SEBUAH PERTANYAAN UNTUK CINTA DAN CERPEN WHAT WE TALK ABOUT WHEN WE TALK ABOUT LOVE - Aulia Dini Syadiah; Dian Hartati (SeBaSa)
This study intends to compare the two short stories entitled Sebuah Pertanyaan untuk Cinta by Seno Gumira Ajidarma with the short story What We Talk About When We Talk About Love by Raymond Carver. This research uses qualitative descriptive, in order to describe the dimensions of love from the two short stories with psychological aspects. The method used is to examine the psychological aspects of the characters, then compare the contents of the two short stories based on the dimensions of love. The object of comparative literature discussed is related to the dimension of love. The library technique is a data acquisition process. The results of this study are that there are various human efforts in exploring the dimensions of love based on psychology. Each of these dimensions affects the behavior of individuals in behaving and thinking when oriented. Therefore, the dimensions of love that are studied by psychology consist of the id, ego, and superego which are then analyzed based on the dimensions of love including, domination, self-process, commitment, attachment, satisfaction, and conflict.